Pengembangan Bahan Ajar Kimia Inovatif Berbasis Multimedia Untuk Meningkatkan Hasil Belajar Siswa Pada Pengajaran Termokimia - Nur Winda Adha; Manihar Situmorang; Zainuddin Muchtar (Pascasarjana Universitas Negeri Medan, 2016)
Abstract. This research aims to develop innovative teaching materials chemistry-based multimedia to improve student learning outcomes in thermochemical material. This study is a Research and Development (R & D). This research was conducted in three schools, namely SMA Negeri 1 Percut Sei Tuan, SMA Taman Siswa, and SMA Al-Hidayah Medan. The sample in this study were selected by purposive sampling taken as many as two classes, experimental and control classes. Classroom teaching experiment were treated using innovative teaching materials chemistry-based multimedia classroom control while using the existing books in school. Prior to this research teaching materials have been assessed by two lecturers and 20 teachers chemical chemistry using a questionnaire BSNP. The results showed that (1) Analysis of the chemical on the material thermochemical book gives an average yield of assessing the feasibility of the contents of 3.61, 3.74 and appropriateness of language for the presentation of the feasibility of 3.59. (2) The components of learning be integrated into innovative chemistry teaching materials have been developed (with video integration laboratory activities carried out by the lab which penelit, integration methods and instructional media, and integration of multimedia learning). (3) Analysis of chemistry teachers and lecturers standard for analysis of the contents of about 4.33 eligibility standards, eligibility standard language of 4.12, and the standard of presentation of the feasibility of 4.20. It shows that the results of chemical analysis for innovative teaching materials based multimedia submitted are valid and do not need direvisi.Sedangkan for assessment of learning that has been developed multimedia gained an average of 3.80 is valid for use and does not need revision. (4) The results of experiments showed an increase chemistry student learning outcomes of each sample, namely: SMA Negeri 1 Percut Sei Tuan has an increased chemical learning outcomes by 69%, the SMA Taman Siswa amounted to 55.41% and the Al-Hidayah Private High School for 51.46%. (5) Analysis of student motivation measurements using innovative teaching materials chemistry-based multimedia teaching materials thermochemical the experimental class is high with an average of 72.94, and there is a positive relationship between learning motivation denagn chemistry student learning outcomes (r2 = 0.969 ) on thermochemical teaching. With the increased motivation of learning outcomes that are known from the results indicated that the results of studying chemistry students who are taught by using innovative teaching materials based multimedia kmia better than the results of studying chemistry students taught without the use of innovative teaching materials chemistry-based multimedia. Keyword: teaching materials, innovative, multimedia, learning outcomes, thermochemical